Effluents quality during the grow-out phase of the amazon shrimp macrobrachium amazonicum - Nogueira, Mayra [UNESP]; Pinto, Fernanda De Rezende; Nunes, Ana Paula [UNESP]; Guariz, Cintia Sobue Lorenzon [UNESP]; Amaral, Luiz Augusto Do [UNESP] (Universidade Federal de Goiás, 2014)
In recent years shrimp culture farms have been one of the most growing sectors in aquaculture. Research has been carried out in order to establish a sustainable production maintaining profit and low environmental impact. Current investigation analyzed source and effluent water produced during the final grow-out phase of the Amazon shrimp (Macrobrachium amazonicum). Twelve natural-bottom ponds, with continuous water flow and stock density comprising 40, 60, 80 and 100 young shrimps/m² were analyzed. The experiment design comprised totally randomized blocks with four treatments and three replications. Microbiological analyses for Escherichia coli was attempted, coupled to physical and chemical analyses for pH, temperature, total suspended solids, total nitrogen, nitrite, nitrate, biochemical oxygen demand and chemical oxygen demand of water supply and pond effluents. Results show that whereas effluent quality complied with current legal rules, there was no significant difference between supply and effluent water for the analyzed variables and between stock densities. Under the conditions investigated and the intensification of culture in the final grow-out phase up to a density of 100 young shrimps/m², the production of M. amazonicum reveals low potential for environmental impact for the variables analyzed.

Nas últimas décadas, a carcinicultura de água doce foi um dos setores que mais cresceu na aquicultura. Muitas pesquisas têm sido realizadas a fim de buscar metodologias para uma produção sustentável, ou seja, lucrativa e com baixo impacto ambiental. Neste contexto, o presente estudo objetivou analisar a qualidade da água de abastecimento e do efluente gerado na fase de crescimento final do cultivo do camarão-da-amazônia (Macrobrachium amazonicum). Foram analisados 12 viveiros de fundo natural, com fluxo contínuo de água e densidade de estocagem de 40, 60, 80 e 100 juvenis/m². O delineamento experimental utilizado foi blocos inteiramente casualizados com quatro tratamentos e três repetições. Foram realizadas análises microbiológicas para Escherichia coli e análises físicas e químicas para pH, temperatura, sólidos totais suspensos, nitrogênio total, nitrito, nitrato, demanda bioquímica de oxigênio e demanda química de oxigênio da água de abastecimento e efluentes dos viveiros. Os resultados revelaram que a qualidade do efluente estava de acordo com a legislação vigente e que não ocorreu diferença significativa entre a água de abastecimento e efluente para as variáveis analisadas. Também não ocorreu diferença significativa entre as densidades de estocagem. Concluiu-se que a produção de M. amazonicum nas condições estudadas e a intensificação do cultivo na fase de crescimento final, até a densidade de 100 juvenis/m², para as variáveis analisadas, apresenta baixo potencial de impacto ambiental.
Qualidade dos efluentes produzidos na fase de crescimento do camarão-da-amazônia macrobrachium amazonicum
Keywords: effluent; environmental impact; shrimp culture; water quality; carcinicultura; efluente; impacto ambiental; qualidade de água